Public Employment Policy Professionals in Industrialized Countries: Different Contexts and Similar Practices - Provencher, Ysabel; Richard, Marie-Claude (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2010)
Based on a review of predominantly French, Canadian and American literature this article deals with employment coaching of populations excluded from the labour market. This is a new function that emerged from the activation of public employment policies over the past few years, and has become now the principal mode of commitment of the state towards populations excluded from the labour market. Focusing on the discourse and practices of counselling professionals, concerning the development of this function, the article highlights the impact of transactions between agents of public policy and their clients on the effects of reforms to social assistance programs. While day to day practices vary among coaching providers according to their specific environments, the literature review shows a convergence of practices among agents of public, private or community employment policies in the use of their own social networks, the constraints they encounter and the strong relational aspects they associate with their counselling function. In concluding, the article notes a lack of awareness of their roles as intermediaries in the labour market, in and in particular about their use of organisational procedures, strategies, and rationale for their actions. S’appuyant sur une recension d’kcrits principalement fran aisc, anadiens et amCricains, cet article traite de l’accompagnement en emploi des populations exclues du march6 du travail, une fonction ayant emerge de l’activation des politiques. Public Employlnent Policy Professionals in Industrialized Countries publiques de l’emploi des dernikres annkes et qui devient le principal mode d’engagement de l ’ t a t envers les populations exclues du march6 du travail. En s’attardant particulikrement aux discours des professionnels de l’accompagnement sur la mise en oeuvre de cette fonction, I’article souligne le rBle des transactions entre les agents des politiques publiques et leurs clients sur les effets des reformes des regimes d’aide sociale. Bien que les pratiques quotidiennes des charges d’accompagnement diffkrent selon les contextes specifiques dans lesquels elles s’inscrivent, des etudes recensges indiquent une convergence des discours des agents des services publics, prives ou associatifs des politiques de l’emploi en ce qui a trait 5 l’utilisation de leur rCseau social, aux contrainces qu’ils rencontrent ainsi qu’5 la forte dimension relationnelle qu’ils associent 2 la fonction d’accomnpagnement. Particle se conclut en constatant le manque d’information lie ii ces acteurs interlnkdiaires du march6 du travail, notamment sur leurs modes d’organisation, leurs strategies et les justifications de leurs actions.